PENGGUNAAN BAHASA INDONESIA DALAM SURAT UNDANGAN PERNIKAHAN LINTAS AGAMA - Masgita Utami, Linda Cahyani (Humanis; Volume 9. No. 1. Oktober 2014)
The use of Indonesian in Interfaith Marriage Invitation Letter is one of the interesting topics to be researched study. This study took a sample of the population and the ongoing wedding invitation letters in 2012, amounting to sixteen wedding invitation letter, especially those located in the region of West Denpasar. This study aims to describe the variation and the use of Indonesian in a wedding invitation letter, describing the meaning contained in the letter wedding invitations, and describe the relation between language letter of invitation to the seven functions of language according to Halliday. The theory used is, semantic theory, the theory of the standard language, descriptive theory, theory perspective, grammatical, words, and spelling. At the stage of data collection used the method of observation (observation) with technical note. Linguistic variation and the use of Indonesian in the invitation letter marriage, is a form of language variation used every religion (Hinduism, Islam, Christianity, and Buddhism) in the opening sentence of the cover letter and wedding invitations. Furthermore, the use of Indonesian component linking the use of paragraphs, sentences, words, and spelling. In the analysis of meaning, the meaning of the analyzed data in the form of messages each sentence in a wedding invitation letter, the meaning of formal, semiformal meaning, the meaning of informal (familiar), meaning a promise, meaning clarity of the topic, the meaning of hope, meaning thank you, and religious meaning. But the meaning of the eight analysis, there is a meaning that is not contained in the letter of the wedding invitation, that is the meaning of informal (familiar). Furthermore, in connection with the use of language -related invitation letters to the seven functions of language according to Halliday, the instrumental function, regulation, interaction, personal, heuristic, imaginative, and reps. Of the seven functions of language, the heuristic function does not have relevance in the use of language wedding invitation letter, because the heuristic function is the use of language that is used to acquire knowledge .
Keywords: forms of linguistic variation, component Indonesian usage, the meaning of the message, and the function of language according to Halliday.